The green prince [videorecording (DVD)] - Schirman, Nadav; Yousef, Mosab Hassan; Yousef, Mosab Hassan; Ben-Itzhak, Gonen; Yousef, Hassan, 1955- (Music Box Films, 2015)
Based upon the true story of the son of a Hamas leader who emerged as one of Israel's prized informants, and the Shin Bet agent who risked his career to protect him.